Anniversary meeting: 30 November 1909 - -, - (Proceedings of the Society of Antiquaries of Scotland, 1910)
The usual business was conducted at the Anniversary meeting, including the election of new Fellows and the presentation of a list of deceased Fellows. An obituary was read for the deceased Arthur Mitchell, a prominent member of the Society’s council. Other reports presented included: A report on the number of Fellows on the Society’s Roll A report on the progress of the Society’s forthcoming publications A note on the Rhind Lectureship from the previous session Reports into excavations undertaken by the Society during the previous session A report on the number of items added to the Society’s museum. Meeting notes for 13 December, 1909 are appended.